Crisis in Black Theology: Reasserting a future based on spiritual liberative praxis - Reddie, Anthony G. (HTS teologiese studies, 2020)
This study explores the contemporary crisis in Black Theology and its present moribund complexion. The author, a well-known black theologian, argues that Black Theology as an academic discipline has struggled with an identity crisis emerging from its origins as a pragmatic response to the existential struggles evinced in the lives of black people and not as an intellectual movement in the first instance. As sociopolitical contexts have changed, a number of scholars have posed the question as to whether there is a continued need for Black Theology. This study outlines the nature of the semantic challenges facing Black Theology and reflects on the importance of Black spirituality (an important theme in the work of Vuyani Vellem) as a means of enabling this form of liberative praxis to better connect to the lived experiences of ordinary black people.Contribution: This article contributes to the ongoing development of black liberation theology across the world. The article focuses on three historic locations where Black theology has traditionally flourished, these being the United States, the United Kingdom and South Africa. In response to the necessity for Black Theology to better relate to the practical realities of ordinary underprivileged black people this article proposes that greater attention should be given to liberative, spiritual praxis.